In vitro digestion of ESC-resistant Escherichia coli from poultry meat and evaluation of human health risk - Buberg, May Linn; Wasteson, Yngvild; Lindstedt, Bjørn Arne; Witsø, Ingun Lund (Frontiers in Microbiology, 2023)
The spread of antimicrobial resistance (AMR) has become a threat against human and animal health. Third and fourth generation cephalosporins have been defined as critically important antimicrobials by the WHO. Exposure to ESC-resistant E. coli may result in consumers becoming carriers if these bacteria colonize the human gut or their resistance genes spread to other bacteria in the gut microbiota. In the case that these resistant bacteria at later occasions cause disease, their resistance characteristics may lead to failure of treatment and increased mortality. We hypothesized that ESC-resistant E. coli from poultry can survive digestion and thereby cause infections and/or spread their respective resistance traits within the gastro-intestinal tract. In this study, a selection of 31 ESC-resistant E. coli isolates from retail chicken meat was exposed to a static in vitro digestion model (INFOGEST). Their survival, alteration of colonizing characteristics in addition to conjugational abilities were investigated before and after digestion. Whole genome data from all isolates were screened through a custom-made virulence database of over 1100 genes for virulence- and colonizing factors. All isolates were able to survive digestion. Most of the isolates (24/31) were able to transfer their blaCMY2-containing plasmid to E. coli DH5-α, with a general decline in conjugation frequency of digested isolates compared to non-digested. Overall, the isolates showed a higher degree of cell adhesion than cell invasion, with a slight increase after digestion compared non-digested, except for three isolates that displayed a major increase of invasion. These isolates also harbored genes facilitating invasion. In the virulence-associated gene analysis two isolates were categorized as UPEC, and one isolate was considered a hybrid pathogen. Altogether the pathogenic potential of these isolates is highly dependent on the individual isolate and its characteristics. Poultry meat may represent a reservoir and be a vehicle for dissemination of potential human pathogens and resistance determinants, and the ESC-resistance may complicate treatment in the case of an infection.